(3GdeMGSHI GdeGdjI GdeYebI s - (3NjQI(B, (3YjThTs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3eMGSHI GdJKHjJGJ GdLGQjI hGdJKHjJGJ GdZjQ GdLGQjI, hcPdc GdJKHjJGJ GdeGdjI eY GdeNRhfGJ hGdfJLGJ bjO GdJfajP, hGdMbhb(B. (3GVGaI Gdi GdOjhf hGdbQhV GdeeGKdI, eY GdGjLGQ GdJehjdj hGdGYGfGJ hGdYbhO Ydi GdeOi GdWhjd heDhfGJ GdeNGWQ hGdCYHGA hcPdc JShjI MSGHGJ GdJSjjQ hJZjjQ GdWQb GdeMGSHjI, hCNjQG JCSjS GdTQcGJ hJZjjQ QCS GdeGd(B.s
(3eQGLY U(B.112s
Keywords: (3GdeMGSHI GdJMdjdjIs; (3GdeMGSHI GdeYebIs